Parallel Curve Detection Method based on Hough Transform: Discrete and Computational Geometry, Graphs, and Games - Chanpaisit, Nattapol; Vatiwutipong, Pat (Thai Journal of Mathematics, 2023)
Hough transform is a widely used approach for recognizing straight lines and circles. Recently, an extension was published, allowing us to detect a larger class of algebraic curves. The image with parallel curves is the subject of this study. An incorrect curve may be detected using the standard approach. We modify the accumulator function and introduce the concept of parallel curves into the detection method to tackle this problem. Synthetic and real-world images are used to demonstrate the effectiveness of this method.